Aplicación del derecho notarial en el ámbito sucesoral - Plúas Cobo, Briggitte Stefania (2025)
The inheritance processes in Ecuador, regulated mainly in the Civil Code and the Notarial Law, involve the sponsorship, the deceased and the heir, around processes surrounding the death of a person and the subsequent granting of their assets, obligations and properties. The objective of this research is to analyze how notarial law is applied to inheritance in Ecuador, identifying the strengths and weaknesses of the system. In this sense, a descriptive legal research was carried out through a study and analysis of Ecuadorian regulations, judicial precedents and notarial practices in countries of the region regarding their application in the field of inheritance and the evolution of the legal framework. The importance of these reforms to protect the rights of heirs, particularly those considered forced heirs, such as spouses and children in inheritance matters, is highlighted. It is concluded that the recent reforms of inheritance law in Ecuador aim at a fairer and more equitable distribution of inheritance assets, however, despite these legislative advances, challenges persist to effectively implement these regulations.